Más allá de la dicotomía realismo-instrumentalismo - Ricardo J. Gómez (Crítica)
My main purpose is to show that (1) the standard characterization of instrumentalism (Duhem) fails to grasp adequately the complexity of the cognitive status of important scientific theories in the past, e.g. Ptolemy's astronomy; (2) that failure is closely related to certain presuppositions which have been recently criticized from different points of view avoiding the dichotomy instrumentalism-realism, and (3) such opposition between instrumentalism and realism has been usually understood in a too extreme, atemporal and global way. I recommend to substitute it by a myriad of more or less strong realisms taking into account not only the different levels and components in a scientific theory, but also the historical circumstances under which its cognitive status is evaluated.